THE INVOLVEMENT OF DIFFERENT VITAMIN TYPES IN ASSISTING THE ACTIVATION OF STEM CELLS: A REVIEW - Hapsari, Tyastuti Prima (Journal of Stem Cell Research and Tissue Engineering, 2024)
Recent research indicates that vitamins play a key role in regulating cellular processes, especially in stem cells. Stem cells are undifferentiated cells with the potential to develop into various cell types and regenerate themselves. The article selection process followed predetermined inclusion criteria and spanned from March 18, 2024, to March 31, 2024, lasting one month. Articles were searched using specific keywords, and those meeting the criteria were selected. Six articles were collected for review, primarily focusing on assessing the role of each vitamin in stem cell survival. Most vitamins studied have shown similar functions in enhancing the viability of stem cells by promoting their differentiation. However, recent research has revealed a unique role for vitamin E in relation to stem cells. Vitamin E acts as a facilitator for mesenchymal stem cells, inhibiting dendritic cells and enhancing their immunomodulatory effects. All these vitamins are pivotal in preserving the wellbeing and functionality of both stem cells and bodily tissues.